The Effectiveness of the POLA (Lantern Light Project) STEM-PJBL Model in Fifth-Grade Student Engagement and Higher-Order Thinking Skills - Ahmad Fajar Mas'udi; Ika Maryani (Sekolah Dasar: Kajian Teori dan Praktik Pendidikan, 2024)
Science education requires students to engage and utilize higher-order thinking skills (HOTS) actively. Effective science instruction should be contextualized to promote comprehension. Key components that support science learning include the use of appropriate instructional models and visual aids or learning media. When teaching models and tools are lacking, knowledge transfer to students is hindered. This study aims to examine the effectiveness of the POLA (Lantern Light Project) model, a STEM-PJBL-based approach, in fifth-grade science lessons on the properties of light, with a focus on student engagement and HOTS. This quantitative study employs a quasi-experimental one-group pretest-posttest design and uses paired sample T-test analysis to assess pre- and post-intervention differences. Results indicate that the STEM-PJBL-based POLA model enhances both engagement and HOTS in fifth-grade students studying the properties of light.